Sourcing and procurement strategy in supply chain management: the case study for Petronas Dagangan Berhad / Nurul Fahmy Latin - Latin, Nurul Fahmy (2009)
The purpose of the study is to explore the sourcing and procurement strategy in terms of supply chain management by PDB. It is to examine the sourcing and procurement in terms of strategy process, supplier relationship, reducing cost, during economic downturn, and competitive advantage. There are three issues arrived in the study which including shortage in supply, responds towards having effective sourcing of demand with other supplier, and source supplies from emerging markets. The researcher uses interview method in order to gain information from the company as well as other secondary data. The findings show that most of the company practice does follow the theory view but there are some differences between them in terms of reducing cost and sourcing and procurement during economic downturn. Findings are useful to develop and measure the competitive capabilities of sourcing and procurement strategy and guide the organisations to enhance supply chain responsiveness and organisational performance. As a result, PDB must have an efficient long term planning as it can’t be implemented in a flash, cooperate with suppliers as to increase the higher production thus will minimize the cost, maintain its sourcing and procurement strategy during economic downturn as it has less effect on sales of product, and maintain pool of suppliers as well as minimizing risk.